A Newly Discovered Greek Father Cassian the Sabaite eclipsed by John Cassian of Marseilles. - Tzamalikos, Panayiotis (Leiden : BRILL, 2012)
A critical edition an ancient manuscript, which has resulted in discovery of Cassian the Sabaite, whom Medieval forgery extinguished, by attributing heavily interpolated Latin translations of this Greek original to a figment called 'John Cassian'. This erudite Sabaite intellectual is Pseudo-Caesarius and the author of Pseudo Didymus' De Trinitate.
Cassian and the Chronicon PaschaleCassian the Astronomer; Conclusion; The Text. Codex Metamorphosis 573, Meteora, folia 209r-209v; Notes to the Text; Bibliography; I. Codices; II. Primary Sources; III. Modern Sources; IV. Ancient Lexica of Greek Language; Index of Persons of Antiquity, Locations, and Notions; Index of Greek Terms, Names, and Expressions; Index of Modern Authors
Description based upon print version of record.
Keywords: Cassian -- the Sabaite -- approximately 470-548.; Church history -- Primitive and early church, ca. 30-600.; Monastic and religious life; Religion; Church history -- Primitive and early church, ca. 30-600.; RELIGION / Institutions & Organizations; Electronic books